BALA TÁRBIYASÍNDA SHAŃARAQ HÁM OQÍTÍWSHÍNÍŃ TUTQAN ORNÍ - Kadrekova, A.; Bekmuratova, V. (SCIENCE and SOCIETY, 2023)
In this article is said about the role of family and teacher in educating a child. It is given recommendations and ideas about it.